Implementation of Peer Tutor Learning Method to Improve Language Skills (Listening, Speaking, Reading and Writing) of Children at Darul Muhsin Kindergarten Group B Through Various Writing Activities - Ilyas, Diyan Hardianti; Fitriani, Fitriani; Markuna, Markuna (International Journal on Advanced Science, Education, and Religion, 2025)
The study aims to determine the application of the Peer Tutor Learning Method to Improve Language Skills (Listening, Speaking, Reading and Writing) of Children in Darul Muhsin Kindergarten Group B Through Various Writing Activities. This study uses a Classroom Action Research (CAR) approach, the subjects of the study were 11 children in Group B2 Ali Bin Abi Thalib TKIT Darul Muhsin Makassar. Data management with Observation, and Implementation Evaluation. The data from the development research are described as The application of peer tutor learning to develop language skills (listening, speaking, writing and reading) in Group B2 TKIT Darul Muhsin is quite effective. The increase can be seen from the results of observations at the end of the improvement of development activities, including: activities to listen to animated videos and learning, speaking and retelling the contents of the videos that have been watched, reading words in the arrangement of letters forming words and writing and drawing activities on the theme of the Universe sub-theme of celestial bodies and natural phenomena. Quantitatively based on the table of results of the final achievement of cycle 2, there has been an increase in language development (listening, speaking, writing and reading) with the help of peer tutors. The increase was from cycle 1 with a value of 2.30 with the predicate Starting to Develop (MB), in cycle 2 it became 3.07 with the predicate Developing According to Expectations (BSH).